Some aspects of the biology of ikan baung, mystus nemurus C. & V with references to Chenderoh reservoir - Khan, Mohammad Salim (Fakulti Pengajian Maritim dan Sains Marin, 2010)
Some aspects of the biology of Ikan Baung, Mystus nemurus C.&V. including taxonomy, food and feeding habits, reproduction, growth and its ecology were studied. The fish is a bottom feeder and fed extensively on a wide range of food items that include teleosts, crustaceans, benthic invertebrates and detrital materials. The relative gut index has been found to vary from the lowest 0.783 to the highest 1.07 in a size range of 8.2 to 67.0 cm.